Unified Field Mechanics 2015
DOI: 10.1142/9789814719063_0012
|View full text |Cite
|
Sign up to set email alerts
|

The Electron is a Charged Photon with the De Broglie Wavelength

Abstract: A charged photon and its light-speed helical trajectory form a surprising new solution to the relativistic electron's energy-momentum equation. This charged photon model is a new model for the electron, and quantitatively resembles the light-speed electron described by Dirac. The charged photon model of the electron is found to quantitatively predict the relativistic de Broglie wavelength of the free electron. This suggests a new interpretation of quantum mechanics, where the electron is seen as a charged phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…We have observed that if ionization energy increases down to the inner most electron, then the absorption of photon decreases down to the inner most electrons as well [9]. Therefore, this clearly shows that while ionization energies are the energies binding the electrons to the nucleus, they are not, necessarily, the energies absorbed by the electrons.…”
Section: The Importance Of a Papcmentioning
confidence: 73%
See 1 more Smart Citation
“…We have observed that if ionization energy increases down to the inner most electron, then the absorption of photon decreases down to the inner most electrons as well [9]. Therefore, this clearly shows that while ionization energies are the energies binding the electrons to the nucleus, they are not, necessarily, the energies absorbed by the electrons.…”
Section: The Importance Of a Papcmentioning
confidence: 73%
“…From each of Figs. 4,5,6,7,8,9,10,11,12,13,14,15, and 16, we can see that in Fig. 4, where z ¼ 4, beryllium is the element with the most potential for photon absorption, followed by z ¼ 6, carbon, and then z ¼ 8, oxygen.…”
Section: Generating a Papc Genome For Materialsmentioning
confidence: 91%
“…A model of a relativistic electron composed of a spin-½ helically-moving charged photon was proposed by Gauthier 10 , while a model of a relativistic electron composed of a helically-moving charged photon was earlier proposed by Gauthier 11 . The charged photon in both of these models would move in a circle in a resting electron.…”
Section: Justifications For Modeling Elementary Particles By a Circulmentioning
confidence: 99%